Adenocarcinoma of Pigmented Ciliary Epithelium in a Child With Aicardi Syndrome and Congenital Microphthalmia With Cyst. Issue 2 (March 2018) - Lira, Jennifer; Berry, Duncan E.; Weller, Christopher L.; Proia, Alan D.; Leyngold, Ilya M.
Abstract : A 5-year-old girl with Aicardi syndrome and microphthalmia with cyst of the OD presented with progressive enlargement of the cyst causing pain. Microophthalmia with inferior cyst (35 × 25 × 12 mm) was noted at birth, and Aicardi syndrome was diagnosed at 10 months by the presence of the classic triad of callosal agenesis, infantile spasms, and chorioretinal lacunae. She underwent enucleation with cyst resection, and subsequent reconstruction with a dermis fat graft. Histopathologic study revealed adenocarcinoma of the pigmented ciliary epithelium. Full-body metastatic workup was negative. Adenocarcinoma of the pigmented ciliary epithelium is an extremely rare eye tumor with only 4 documented cases in the literature, none arising in a microophthalmic eye with cyst. Aicardi syndrome is also a rare disease that has been associated with increased incidence of malignancy and ocular abnormalities, but has never been described in association with microophthalmia with cyst or with adenocarcinoma of the pigmented ciliary epithelium. Herein, the authors present a review of the case and relevant literature. Abstract : The authors present a case of adenocarcinoma of the pigmented ciliary epithelium arising in the microphthalmic eye with cyst in a 5-year-old girl with Aicardi syndrome.